Prestack time imaging algorithm with simultaneous velocity estimation in hard rock environments - Tertyshnikov, Konstantin; Bona, Andrej; Pevzner, Roman (CSIRO Publishing, 2013)
Reflection seismic imaging faces several difficulties in hard rock environments. One of them is the estimation of the propagation velocity of seismic waves. Therefore, imaging algorithms that do not require prior construction of a velocity model seem promising for such environments. In this paper we illustrate an application of prestack time migration, which does not require an input velocity model, to hard rock conditions, and we demonstrate its effectiveness on synthetic data. This approach is based on an estimation of local event slopes (horizontal slownesses) in common-shot and common-receiver gathers and a subsequent calculation of the migration attributes (migration velocity, vertical traveltime and horizontal coordinates of the migrated reflection point). These attributes allow us to derive all the information needed to construct a time migrated image. We also use the obtained migration velocities as an input velocity model for Kirchhoff prestack time migration (PSTM) and compare the results of the proposed approach with a conventional Kirchhoff migration using as an input the pickedNMOvelocity model. This application to a hard rock synthetic model illustrates the potential of the presented migration algorithm for imaging in hard rock seismic exploration. We believe that this approach can be used in hard rock seismic processing workflows as an automatic tool to obtain an input velocity model for the Kirchhoff PSTM.